Dual and Unilateral Commitment Among Stewards and Rank-and-File Union Members - Magenau, John; Martin, James E.; Peterson, Melanie M. (Academy of Management Journal, 1988)
This study investigated commitment patterns among stewards and among rank-and-file union members. Stewards had a higher frequency of both dual and unilateral union commitment than did the rank and file. Positive union-management relations, high job satisfaction, and positive union decision-making practices were consistently related to high dual commitment. High union involvement, positive perceptions of union decision-making practices, and low job satisfaction were consistently related to unilateral union commitment. An explanation of the findings based on exchange theory is offered.